Improved Learning Summarizes Short Stories with Problem-Based Learning Models - Herni Mahavira (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
This article describes the improvement of learning to summarize short story text with Problem Based Learning (PBM) model. The method used in this research is Classroom Action Research. Sources of data in this study were students of class VII-1 consisting of 18 men and 18 women. The results showed that learning to summarize short story text with PBM model can improve learning attitudes, learning activities, and student learning outcomes. The results of the questionnaire, the value of teacher observation, the value of student observation was categorized high and increased in each cycle, the results support the increase in student learning outcomes in learning to summarize short story text using the PBM model. Keywords: Short story, Problem Based Learning (PBM).